Aceitação do uso de recursos tecnológicos pelos docentes de pós-graduação em Contabilidade - Nganga, Camilla Soueneta Nascimento (2015)
Due to the increasing insertion of technological resources in education and the transformation of educational processes, there is the need to study and understand the processes that underlie the acceptance of the use of technology in education. In this context, the aim of this study was to identify and analyze the factors that influence the acceptance of the use of technological resources applied in stricto sensu postgraduate courses in accounting, focusing on the perception of teachers and considering the changes that the accounting has been suffering, especially the expansion of stricto sensu postgraduate programs in that area. The outline of this study was based on the Unified Theory of Acceptance and Use of Technology, also known as model UTAUT, which points to the following factors that affect the intended use of technology: Facilitating Conditions, Performance Expectancy, Effort Expectancy and Social Influence. The study was characterized as descriptive and had a quantitative approach through the application of Confirmatory Factor Analysis, Multiple Regression Analysis and in a complementary way, the Mann-Whitney Test (U Test). The survey results indicated that the constructs Performance Expectancy and Effort Expectancy were those with significant effect on the Intention to Use of technological resources by teachers of postgraduate program in accounting, and these constructs showedstandardized coefficient of regressionequal to 0,553 and 0,268, respectively, and statistical significance in relation to the t-test. The R2 of the model tested was 0,702, showing that 70,2% of the variation that occurs in the Intention to Use can be explained by the model of independent variables. Regarding Performance Expectancy construct, it infersthat teachersbelieve that the use of technological resources helps in improving the quality of classes, in performing tasks more quickly and can also help in improving student sperformance. In relation to the construct Effort Expectancy and considering its statistical significance,the acceptance and use of technologies in the postgraduate program in accounting assists in facilitating the conduct of classes. It is important to emphasize that surveyed teachers may have certain ease in acquiring skills to use technology.